A practical action perspective and understanding on becoming a networked learning educator - Hodgson, Vivien; Watton, Emma; Ralph, Neil (Proceedings of the International Conference on Networked Learning, 2016)
In the paper we examine one of the enduring issues in networked learning of the reticence of academics to work with and/or run networked learning courses mediated by technology. The paper is based on an analysis of the situated practice of members of an academic department and the work done in becoming a networked learning educator. It builds on the recent interest in practice based studies (PBS) that has led to an increase in looking at learning and knowing through the doing of practice. Following Schatzki, (2001) we see practice as an embodied and materially mediated activity around practical understanding. The research approach we have chosen to look at this is that associated with ethnomethodology; which has a long-standing interest in the understanding of practical action. In the paper we offer an account of the social fact of the competent university teacher as constructed in what Garfinkel (1967) refers to as ‘common understanding’ exhibited in the methods used and descriptions of practice-in-action of members of the department. Further we suggest that members of the department exhibited three emerging practical understandings of a networked learning pedagogy; - Need to have an integrated design framework to a NL programme that is clear to students but also to staff - Any such framework needs to be able to accommodate differences in personal staff styles and ways of engaging with students - The framework should build on existing understandings, methods and work done by members on the development of pedagogical design and frameworks We go on to examine an account of designing an online module and the practice-in-action exhibited by Emma, one of the authors, in becoming a networked learning educator. For illustrative purposes we focus on the methods used and work done in Emma’s practice-in-action in an account entitled 'shifting responsibility to students'. We conclude with the suggestion that the pattern and rhythm of the module could be used as a starting point for a pedagogical framework that can accommodate and/or exhibit the practical understanding of pedagogy for members of the department.